Computers and application software - Szymanski, Robert A.; Szymanski, Donald P.; Morris, Norma A.; Pulschen, Donna M. (Columbus : Merrill Publishing Company, 1988)
The existence of this text confirms the relevance and importance of the new technologies of the Information Age. From the contract negotiation stage when the publishing company ran computer budgeting and production analyses, to the drafting.
Chapter 1. A world with computer -- Chapter 2. Computer essentials -- Chapter 3. Computer system -- Chapter 4. Communication and networks -- Chapter 5. Information system -- Chapter 6. Programming concepts and operating system -- Chapter 7. Introduction to application software -- Chapter 8. Word processor -- Chapter 9. Data managers -- Chapter 10. Spreadsheets -- Chapter 11. Graphics packages -- Chapter 12. Communication packages.
Includes index.
Keywords: SOFTWARE